Characterisation of Axonopus compressus fibre through chemical composition, thermogravimetric behaviour, and moisture content evaluation - Jumaidin, Ridhwan; Wahid, Mohammad Khalid; Mohd Suan, Mohd Shahadan; Md Yusof, Fahmi Asyadi (Penerbit Akademia Baru, 2023)
The thermal properties and moisture content of Axonopus compressus, a common grass species used for various purposes, have received insufficient attention. This study aims to investigate these facets, utilising insights from previous research on the plant's numerous applications, such as soil erosion prevention, water purification, and heavy metal pollution treatment. The study extracted Axonopus compressus fibre from Melaka, Malaysia, using the water retting method and analysed its chemical composition using neutral detergent fibre (NDF), acid detergent fibre (ADF), and acid detergent lignin (ADL) according to ISO standards. The results indicated a chemical composition of 27.28 % cellulose, 22.56 % hemicellulose, and 4.79 % lignin. Thermal gravimetric analysis (TGA) was used to determine the fibre's thermal stability and decomposition behaviour. The initial decomposition temperature of the fibres was 228°C, with maximum decomposition occurring at 360 °C. In addition, the moisture content was measured at 14.95 %.